Future changes in δ 13 C of dissolved inorganic carbon in the ocean - Graven,H; Lamb,E; Blake,D; Khatiwala,S (Earth's Future, 2021)
Emissions of carbon dioxide from fossil fuel combustion are reducing the ratio 13C/12C, δ13C, in atmospheric urn:x-wiley:23284277:media:eft2900:eft2900-math-0001 and in the carbon in the ocean and terrestrial biosphere that exchanges with the atmosphere on timescales of decades to centuries. Future changes to fossil fuel emissions vary across different scenarios and may cause decreases of more than 6‰ in atmospheric δ13urn:x-wiley:23284277:media:eft2900:eft2900-math-0002 between 1850 and 2100. The effects of these potential changes on the three-dimensional distribution of δ13C in the ocean has not yet been investigated. Here, we use an ocean biogeochemical-circulation model forced with a range of Shared Socioeconomic Pathway (SSP)-based scenarios to simulate δ13C in ocean dissolved inorganic carbon from 1850 to 2100. In the future, vertical δ13C gradients characteristic of the biological pump are reduced or reversed, relative to the preindustrial period, with the reversal occurring in higher emission scenarios. For the highest emission scenario, SSP5-8.5, surface δ13C in the centre of Pacific subtropical gyres falls from 2.2‰ in 1850 to -3.5‰ by 2100. In lower emission scenarios, δ13C in the surface ocean decreases but then rebounds. The relationship between anthropogenic carbon (Cant) and δ13C in the ocean shows a larger scatter in all scenarios, suggesting that errors in δ13C-based estimates of Cant may increase in the future. These simulations were run with fixed physical forcing and ocean circulation, providing a baseline of predicted δ13C. Further work is needed to investigate the impact of climate-carbon cycle feedbacks on ocean δ13C changes.